Frequency of Hypomagnesemia in Neonates presenting with Hypocalcemia in a Tertiary Care Hospital - Nadia Ejaz, Sumera Abdul Karim, Faiza Pervaiz, Arwa Ejaz, Misbah Nargis, Shumaila Talib (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Hypocalcemia is a common neonatal occurrence, especially in neonates with high-risk including those babies born to diabetic mothers, neonates with perinatal asphyxia and premature babies. High calcium consumption can reduce magnesium absorption, while low magnesium intake can boost calcium absorption. Aim: To assess the frequency of hypo-magnesemia in neonates presenting with hypocalcemia in a tertiary care hospital. Design study: Cross sectional study. Methodology: Total 160 fulfilling the inclusion criteria at Services Hospital, Lahore were enrolled through non-probability convenience sampling. Gestational age, birth weight, gender and feeding pattern) were noted. Blood sample was obtained by using 3cc BD syringe and 20G butterfly needle with the help of a nurse under sterile measures. All clotted samples were stored and sent to the Pathology lab for the assessment of magnesium level. Reports were assessed and if magnesium level<0.7mmol/L, then hypomagnesemia was labeled. Data was evaluated by using SPSS v.24. Quantitative data was presented as mean±SD. Qualitative data was presented as frequency and percentage. Chi-square test was applied with P-value ≤0.05 taken as significant. Results: In this study, there were 75 (46.9%) male and 85 (53.1%) female neonates. The mean gestational age of neonates was 39.20±1.63weeks. The mean birth weight of neonates was 2.5±3.0kg. There were 46 (28.8%) who were on exclusive breast feeding, 55 (34.4%) were on formula feed while 59 (36.9%) were on both; breast and formula feed. The mean magnesium level of neonates was 0.90±0.63mmol/L. There were 113(70.6%) neonates with hypomagnesemia while 47 (29.4%) had normal magnesium level. Practical Implication: Literature has reported that the frequency of hypomagnesemia is high in neonates with hypocalcemia. In Pakistan there is little local evidence available in this regard. The information gained through this study will help to improve our clinical practice and to update guidelines for early screening and management of infants with hypocalcemia with co-existence hypomagnesemia. Conclusion: It was concluded that the frequency of hypo-magnesemia was high in neonates with hypo-calcemia in local population. Keywords: Prevalence, Calcium, Electrolytes Imbalance and Neonates.